Plant remains (Scottish Historical and Archaeological Internet Reports, 2001)
The composition of the charred plant assemblage through all phases of deposition reflects a striking consistency. Oats predominate throughout with lesser quantities of barley, wheat and weed seeds. This probably reflects the use of these cereals throughout the occupation of the site, with oats being the most popular in all periods. Indeed this shows very much the trend for the high medieval period in Scotland. Investigations at Perth, for instance, found that oats and barley were the most frequently recovered cereals there too. Unfortunately it has not been possible to determine whether the crops at Dundrennan were locally grown. Certainly, the weed assemblage, indicating sandy acid soils, could have come from local fields.